(untitled) (Journal of Training and Development, 2015)
This paper explores the impact of ten years armed conflict on Nepalese People, analyzing how these people are coping the situation in post conflict. Some international practices for conflict victim’s related literature are also presented here. It then considers the forms of reparation and how human rights principles, particularly those regarding the best interests and evolving capacities of the people can help guide program design through TVET program. Ultimately, this analysis shows that people-oriented reparations should be tailored to people’s particular vulnerabilities, needs, and circumstances. DOI: http://dx.doi.org/10.3126/jtd.v1i0.13087 Journal of Training and Development Vol.1 2015: 27-32